(untitled) (Journal of Applied Learning and Teaching, 2022)
Assessments and feedback are interrelated and play a vital role for students, educators, and institutions. However, giving feedback can be daunting for educators and receiving feedback can be unsatisfactory for students, diminishing the effectiveness of further improvement of students’ learning. This research reviews recent literature from 2017 onwards to identify students’ and educators’ challenges in assessing their perceptions and experiences of the feedback process. Additionally, it reviews the literature about what feedback means and the features that make feedback effective. This research proposes five key areas, namely: (i) content; (ii) tone and language; (iii) feedback literacy, (iv) educator training; and (v) assessment design and marking guidelines, for educators and their institutions to improve the feedback process, thereby improving the learning experiences of students.